2010
DOI: 10.1111/j.1440-1754.2010.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐year prospective surveillance of healthcare‐associated infections in a neonatal intensive care unit from southern part of Turkey

Abstract: In this study, the overall infection rate is high compared with developed countries and predominant micro-organisms are gram-negative enteric rods. These results strongly suggest the need for improving measures for prevention and control of HAIs in this hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
2
18
1
6
Order By: Relevance
“…This specificity is not found in most studies in the international 3,4,5,19 or national 8,15,21 literature. Although coagulase-negative Staphylococcus is the most important microorganism of sepsis reported in literature, [3][4][5]7,8,15,21 difficulties were found in fulfilling the infection criteria associated to this microorganism because two blood culture samples are necessary to notify LCBI. 10 This fact limits comparisons of this study with others, but better enables targeted actions in the studied location.…”
Section: Also In Italy Risk Factors For Infection In Very Low Birth contrasting
confidence: 44%
See 1 more Smart Citation
“…This specificity is not found in most studies in the international 3,4,5,19 or national 8,15,21 literature. Although coagulase-negative Staphylococcus is the most important microorganism of sepsis reported in literature, [3][4][5]7,8,15,21 difficulties were found in fulfilling the infection criteria associated to this microorganism because two blood culture samples are necessary to notify LCBI. 10 This fact limits comparisons of this study with others, but better enables targeted actions in the studied location.…”
Section: Also In Italy Risk Factors For Infection In Very Low Birth contrasting
confidence: 44%
“…Comparison among countries also reveals wide variation, with incidence densities of 3.6 to 18.1 infections per 1,000 patient-days in the United States, 1,2 from 6.9 to 7.8 infections per 1,000 patient-days in Italy, 3,4 from 10.9 to 17.3 infections per 1,000 patientdays in Turkey, 5 and 28.6 infections per 1,000 patient-days in a German center. 6 In Brazil, a multicenter study found 25 infections per 1,000 patient-days, 7 similar to data obtained in a private hospital in São Paulo (23.8 infections/1,000 patient-days).…”
Section: Introductionmentioning
confidence: 96%
“…In another study, researchers reported that S. aureus was the most frequent pathogen of bloodstream infections in a Turkish neonatal intensive care unit in 2001. However, after five years, that bacterium became the fourth frequent agent following three Gram-negative species, and responsible for only 10% of all cases (13). Nevertheless, there is still data paucity on the current situation of the HAI pathogens and their antimicrobial resistance in Turkey, particularly in the current decade.…”
Section: Introductionmentioning
confidence: 99%
“…The first two extremely premature patients died; probably, the microorganism was resistant to imipenem and meropenem. These are two of the mostly used first‐line antibiotics for health care‐associated infections in our unit, as we have mostly gram‐negative infections 23,24 . The limitation of this study is that we could not study the genotyping of all the grown microorganisms of the patients.…”
Section: Discussionmentioning
confidence: 99%